Predictors of Functional Cure of Chronic Hepatitis B Virus Infection: A Long-Term Follow-Up Study - Wu, Jia-Feng; Tai, Chi-San; Chang, Kai-Chi; Chen, Yuh-Jue; Hsu, Chien-Ting; Chen, Huey-Ling; Ni, Yen-Hsuan; Chang, Mei-Hwei (Clinical gastroenterology and hepatology, 2025)
A functional cure is an essential endpoint in the management of patients with chronic hepatitis B virus (HBV) infection. We evaluated the cumulative probability and predictors of functional cure in patients with chronic HBV infection after hepatitis B e antigen (HBeAg) seroconversion. We retrospectively analyzed 413 (249 males and 164 females) initially HBeAg-positive chronic HBV–infected patients who were followed up for a mean of 26.36 ± 0.53 years. All underwent HBeAg seroconversion during follow-up. A functional cure was defined as durable HBsAg and HBV DNA loss without antiviral treatment for more than 24 weeks. After 10,888 person-years of follow-up, the cumulative probability of functional cure was 14.53% (n = 60). There were 24 (40%) subjects with functional cure after antiviral therapy. The annual functional cure rate was 0.55% per person-year, and increased to 0.96% per person-year after HBeAg seroconversion. In subjects with functional cure, the HBsAg and HBV DNA titers after HBeAg seroconversion were positively correlated with the time to functional cure (P < .001 and < .001, respectively). Multivariate Cox proportional hazards analysis of the cohort revealed that HBeAg seroconversion at <18 years of age, high-genetic-barrier nucleos(t)ide analogue(s) therapy before HBeAg seroconversion, and a serum HBsAg titer <1000 IU/mL at 18 months after HBeAg seroconversion were significant predictors of functional cure (P < .001, .001, and .001, respectively). In a cohort of chronic HBV–infected patients with long-term follow-up, HBeAg seroconversion in childhood, high-genetic-barrier nucleos(t)ide analogue(s) therapy, and low HBsAg titers after HBeAg seroconversion were significant predictors of functional cure.